1998
DOI: 10.1046/j.1365-2796.1998.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of routine transthoracic echocardiography in evaluation and management of stroke

Abstract: Objective. To determine the value of routine transthoracic echocardiography in patients with cerebral ischemia without known cardiac disease. Design. The literature from 1990 to 1995 was searched and relevant bibliographies from these papers reviewed. Articles reporting the prevalence and/or risk of stroke for myxoma, vegetation, mitral stenosis, left atrial thrombus, left ventricular thrombus or cardiomyopathy, patent foramen ovale, and atrial septal aneurysm were used. Prevalences and recurrent stroke risk w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…This is a more difficult decision for patients without clinically evident cardiac disease, as these investigations are likely to be of low yield. 8 Although an abnormal ECG is associated with a higher yield of CSE found on echo (17% versus 5% in those with normal ECG), we have found that screening out patients with a normal ECG would miss approximately 30% (13/41) of patients with possible CSE. Thus, ECG alone does not appear to be sensitive enough to identify the approximately 10% of patients in our group, whose echocardiogram demonstrated a diagnostic abnormality for cardiac source of embolus.…”
Section: Discussionmentioning
confidence: 65%
“…This is a more difficult decision for patients without clinically evident cardiac disease, as these investigations are likely to be of low yield. 8 Although an abnormal ECG is associated with a higher yield of CSE found on echo (17% versus 5% in those with normal ECG), we have found that screening out patients with a normal ECG would miss approximately 30% (13/41) of patients with possible CSE. Thus, ECG alone does not appear to be sensitive enough to identify the approximately 10% of patients in our group, whose echocardiogram demonstrated a diagnostic abnormality for cardiac source of embolus.…”
Section: Discussionmentioning
confidence: 65%
“…[1] reported that the mean prevalence of echocardiographic abnormalities in the medical literature for patients older than 45 years presenting with IS or transient ishemic attack was 0.1% for myxoma, 1.0% for vegetations, 2.0% for mitral stenosis, 0.3% for left atrial thrombi, 10.0% for cardiomyopathy, 9.0% for LV thrombi/ patent foramen ovale/atrial septal defect, and 3.0% for atrial septal aneurysm. An abnormal LV ejection fraction was present in 5 of 47 patients (11%) with SAH [6].…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic 2-dimensional echocardiography (TTE) has been used in the diagnosis and management of ischemic stroke (IS) with conflicting data as whether it should be considered an essential test in all IS patients in sinus rhythm [15]. Few data are published on TTE in patients with subarachnoid hemorrhage (SAH) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Transthoracic echocardiography is part of the routine investigation of cardiac source of embolus in patients who have experienced stroke in many centres across the world,6 7 but guidelines vary. A recent hospital-based study from Canada reports that transthoracic echocardiography has a low yield, diagnosing abnormalities suggestive of cardioembolic aetiology in only 4% of patients who are ischaemic and have experienced stroke 8.…”
Section: Discussionmentioning
confidence: 99%